Body Image In Female Medical Students, Syarif Hidayatullah State Islamic University, Jakarta, Indonesia: Descriptive Study - Tasya Qonitah Salsabila; Marita Fadhilah; Isa Multazam Noor (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2022)
Background: Body image issues can be a problem for undergraduate female college students. It happened because women pay more attention to their physical appearance than men. In addition, the ages of undergraduate female college students are generally in the young adult age range, where young adult women are found to often experience problems related to body image. Furthermore, some characteristics of campus life may cause female students to be more susceptible to body image concerns. This study aimed to describe the body image in preclinical female students of the Faculty of Medicine, Syarif Hidayatullah State Islamic University Jakarta. Methodology: This study is an observational analytic study with a cross-sectional approach that applied to preclinical female students of the Faculty of Medicine, Syarif Hidayatullah State Islamic University Jakarta, which was selected using the cluster random sampling method. Data were collected by looking at respondents' answers to The Body Appreciation Scale-2 (BAS-2) questionnaire to assess the body. Results: In this study, 120 respondents were collected from the class of 2018, 2019, and 2020 with the age range of 18-22 years. Based on the results of this study, it is known that the majority of research respondents have a negative body image (58.33%). Conclusion: The majority of research respondents have a negative body image (58.33%).